Tempat Sampah Otomatis Berbasis Mikrokontroler Arduino - Handika Sanjaya; Nelly Khairani Daulay; Juni Trianto; Refdi Andri (STMIK Budi Darma, 2022)
Waste management that is not integrated well causes a lack of public interest in disposing of garbage in its place. The impact caused can disrupt the health and cleanliness of the environment. Environmental cleanliness is an important thing that must be considered, a clean environment makes us feel serene and comfortable so it is very important to grow awareness in maintaining environmental cleanliness by disposing of garbage in its place. The method used in this study is the design of the tool, with the needs of analysis, field circuit, tool making, testing and analysis tools. It needs innovation in today's hygiene system technology, one of which is making automatic trash cans to be more efficient in its use. By utilizing technology in its controlling system. A microcontroller-based automatic trash can be made to open and close the box automatically by using the Distance Sensor Control (Ultrasonic) and the servo motor function as the drive cap automatically. Automatic trash can with a microcontroller-based ultrasonic sensor can detect movements with a distance of 30 cm after it automatically servo open the garbage box lid, and delay for 5 seconds